Effect of Sodium Bentonite and Comparison of Pellet vs Mash on Performance of Broiler Chickens - Salari, S.; Kermanshahi, H.; Moghaddam, H. Nasiri (International Journal of Poultry Science, 2005)
An experiment was conducted to study the effect of Sodium Bentonite (SB) and comparison of feed forms (pellet vs mash) on broiler performance. 320 day-old Cobb strain male broiler chickens were allocated to 8 experimental diets with 4*2 factorial arrangements in a completely randomized design. Treatments were 0, 1, 2 and 3 percent of SB and two forms of diets (pellet and mash). At 49 days of age, chickens that fed pelleted diets, consumed more feeds and showed better weight gain and feed conversion ratio (P< 0.05). Pelleting the diets also significantly increased weight of abdominal fat and decreased thigh percentage (P< 0.05). Chickens fed diets containing 1-2 % SB consumed more feed, had more weight gain and less feed conversion ratio (P< 0.05). Under the conditions of this study, it seems that pelleting the diets and 1-2% of SB, improves performance of broiler chickens.